Exploring the incidence of strategic improvisation: evidence from Malaysian Government Link Corporations - Ahmad Arshad, Darwina; Razalli, Mohd Rizal; Abu Bakar, Lily Julienti; Ahmad, Hartini; Mahmood, Rosli (Canadian Center of Science and Education, 2015)
In today’s dynamic business environment, organizations have faced many challenges to stay abreast of changes in order to make wise decisions and best management system.This means that strategic improvisation can be one of the best ways to reconcile organizational tensions.However, the importance of strategic improvisation in the business remains unclear and research in this area is still relatively underdeveloped.To fill this gap, this research is central to explore the incidence of strategic improvisation (SI) in the context of Government Link Corporations (GLCs) in Malaysia. Specifically, this research seeks to examine the relationship of Talent Management (TM) and Entrepreneurial Orientation (EO) with the incidence of SI.Further, SI is also examined to have significant effects on GLCs performance. 281 managers from Malaysian GLCs were used as a sample of the study.The findings confirmed that TM and EO have a positive significant relationship with SI; and there is a positive significant link between SI and GLCs performance.Given the lack of studies on these relationships in previous literatures, it is believed that this research will contribute to the body of knowledge as well as the managerial implication particularly on the GLCs setting.